TINGKAT PENDIDIKAN PERAWAT DENGAN PERILAKU CARING PADA PASIEN DI RSUD DATU BERU TAKENGON - Jek Amidos Pardede; Masri Saragih; Ellyna Yulistiami (Jurnal Online Keperawatan Indonesia, 2020)
Caring is a dynamic approach, in which nurses work to further increase their attention to the clients. Generally, clients would expect the comfort and caring attitude from nurses, and nurses are also expected to provide attention, prayers, and motivation to the patients. The purpose of this study was to identify the correlation of nurse education level with the caring behavior at the inpatient ward of Datu Beru Hospital of Takengon in 2018. This research applied the analytic correlation method using a cross-sectional approach. The population of this study was all nurses working at the inpatient ward of Datu Beru Hospital with a total number of 196 persons. The sampling technique was simple random sampling with total respondents of 67 persons. To obtain data from the respondents the researcher used a questionnaires sheet that was analyzed using chi-square test analysis. This study found that the majority of the nurses hold D3 Degree (59,7%) and the majority of the nurses’ behavior was good (47,8%). The result statistic test showed that there was a correlation between nurse education level and caring behavior on the patients at the inpatient ward with p-value = 0,028 (P <0,05), thus it was concluded that the level of education of nurses correlated with the caring behavior of nurses in the inpatient care room because the higher level of nurses education, the better-caring behavior was provided towards their patients. The results of this study became inputs for nurses to pursue further studies to improve their insight into caring behavior in providing nursing care.